REGULATORY AND TECHNICAL BASIS FOR THE HAZARD ANALYSIS AND CRITICAL CONTROL POINT SYSTEM IN BEEKEEPING ACTIVITIES - Lima, Catarina Pereira; Silva, Mayra Conceição Meira; Santos, Wagner Silva dos; Ferreira, Renata Gabriela Chaves; Freire, Aureliane Aparecida de Araújo; Santos, Hércules Otacílio; Almeida, Anna Christina de; Calaça, Paula; Santos, Eliane Macedo Sobrinho (Veredas do Direito, 2026)
This study aimed to integrate regulatory and technical frameworks with a case study in honey houses, for the implementation of the Hazard Analysis and Critical Control Points (HACCP) system in the beekeeping chain of the Jequitinhonha Valley, Minas Gerais, focusing on compliance with legislation and food safety. The integrated methodology combined document analysis, mapping of SDA Ordinance N°. 795/2023 - Brazil and review of other legislation. In addition to a case study, there is an evaluation of five beekeeping units and microbiological diagnosis. The analyses highlighted the high level of legal requirements, which, although fundamental, represent a cost challenge for low-capital family beekeeping. The on-site evaluation revealed challenges regarding infrastructure and management, which served as preventive indicators. The microbiological diagnosis reinforced the need for control, even though the presence of pathogens was below the legal alert limits, signaling the importance of hygiene in handling and the control of humidity and temperature. The analysis (SWOT matrix) positioned HACCP as the main strategic tool for risk prevention. The study culminated in the proposal of an HACCP plan, which synthesizes regulatory requirements and the need to control proven risks in the field. Therefore, it focuses on critical control points (CCPs) that mitigate biological risk (W1, W3, and W4) and infrastructure challenges (W2), including the development of a simplified registration tool.